HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL DENGAN KEPATUHAN PEMERIKSAAN LAB TRIPLE ELIMINASI (PEMERIKSAAN HEPATITIS, SIPILIS, HIV) PADA IBU HAMIL DI UPT.PUSKESMAS LEDOKOMBO KABUPATEN JEMBER - Fatmiasih, yenny Widiya (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2023)
In accelerating the reduction of morbidity and mortality, the government issued the Minister of Health Regulation Number 52 of 2017 concerning Guidelines for the Elimination of Transmission of HIV, Syphilis and Hepatitis B from mother to child. Therefore, pregnant women need to be given information about HIV, syphilis and hepatitis B which aims to increase the knowledge of pregnant women in transmitting the virus. Based on the K1 report achievement data for January-March 2022 at the Ledokombo Health Center there are 214 pregnant women, 206 new pregnant women were tested for PITC LAB with results 4 positive PITC mothers and 2 HBsAg positive mothers, 8 mothers had not been checked, checked during delivery with positive PITC 1 This research aims to determine whether there is a relationship between the knowledge level of pregnant women and compliance with the Triple Elimination Examination at the UPT Puskesmas ledokombo. This study is a correlative research with a cross sectional approach. The population in this study were pregnant women in the working area of ​​the Ledokombo Health Center UPT aged 20-35 years, involving 72 participants. The side technique used is Simple Random Sampling. Data were collected using a questionnaire. Based on the form of the data scale, in this study using nominal - nominal, the expected count value is less than 5, then the alternative test uses Fisher Exact. The results of the study based on cross tabulation showed that mothers with no knowledge showed proportionally (50%) disobedient and obedient: in mothers with knowledge level of knowledge showed most of them were obedient (70.3%) and the rest (29.7%) were not obedient. Data analysis shows that the data has an expected account < 5, this indicates that it cannot be read using chi square analysis, so that the hypothesis must be drawn using the fiher exact test. Based on the Fisher exact test, it is known that the P-value of 0.220 means that there is no relationship between variablePengetahuan and variable Kepatuhan, which means that knowledge is not related to compliance.